Hubungan Antara Ragam Gaya Belajar (Visual, Auditorik, Kinestetik) dengan Motivasi dan Prestasi Belajar Siswa di SMP Amal Mulia 2 Cileungsi - Julinda Siregar; Laila Eka Rahmantika; Rani Fitriani; Rhisma Putri; Rani Nurhayati; Indriyani; Ummi Lailatun (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to examine the relationship between learning style variations (visual, auditory, and kinesthetic) and students’ learning motivation and academic achievement. The research employed a quantitative approach with a correlational method. The population consisted of junior high school students, with a sample of 100 participants selected using purposive sampling. Research instruments included validated questionnaires on learning styles and learning motivation, as well as documentation of students’ academic scores as indicators of achievement. Data were analyzed using the Pearson Product Moment correlation test to determine the relationships among variables. The results showed a positive and significant correlation between learning styles and learning motivation (r = 0.56; p < 0.05), and between learning styles and academic achievement (r = 0.48; p < 0.05). Students whose learning styles matched the instructional methods demonstrated higher levels of motivation and achievement compared to those whose styles were mismatched. These findings highlight the importance of understanding students’ learning styles as a foundation for developing more effective and adaptive teaching strategies